Possible opportunities and challenges for traditional Chinese medicine research in 2035 - Huang, Nanqu; Huang, Wendi; Wu, Jingjing; Long, Sheng; Luo, Yong; Huang, Juan (Frontiers in Pharmacology, 2024)
The drug development process is poised for significant transformation due to the rapid advancement of modern biological and information technologies, such as artificial intelligence (AI). As these new technologies and concepts infiltrate every stage of drug development, the efficiency and success rate of research and development are expected to improve substantially. Traditional Chinese medicine (TCM), a time-honored therapeutic system encompassing herbal medicine, acupuncture, and qigong, will also be profoundly impacted by these advancements. Over the next decade, Traditional Chinese medicine research will encounter both opportunities and challenges as it integrates with modern technologies and concepts. By 2035, TCM is anticipated to merge with modern medicine through a more contemporary and open research and development model, providing substantial support for treating a broader spectrum of diseases.